LITHOSTRATIGRAPHY AND DEFORMATION HISTORY OF THE LAGO NERO UNIT (CHENAILLET MASSIF, WESTERN ALPS) - Levi, Nicola; Marroni, Michele; Pandolfi, Luca (Ofioliti, 2004)
In the Western Alps, the Schistés Lustrés includes ophiolitic units that, even if affected by HP metamorphism, are relatively poorly deformed. Among them, the Lago Nero unit displays a thick and well-developed sedimentary cover, that allows a comparison with the analogue successions of the Northern Apennines. This sedimentary cover includes hemipelagic deposits, represented by Radiolarite Fm., Metalimestone and Replatte Fm., showing a transition to turbiditic (Gondran Flysch) and mass-gravity deposits (Rocher Renard complex). This succession, characterized by a coarsening upward trend, records the approaching of an oceanic floor section to the accretionary wedge. In this picture, the Rocher Renard complex can be regarded as a formation related to a frontal erosion of the accretionary wedge, whereas the Gondran Flysch is interpreted as a turbidite deposits supplied by the continental margin of the Europe plate. The following deformation history includes four deformation phases. The first phase D1 deformations, characterized by HP metamorphism (lawsonite±Na-amphibole±phengite), were achieved during the coherent underplating in the alpine subduction zone. The D2, D3 and D4 phases was developed under retrograde metamorphic conditions, from grren-schist to very-low grade, during the progressive exhumation of the Lago Nero unit. All the collected data suggest that the succession of the Lago Nero unit can be correlated with those of the Internal Liguride units where the same sequence of hemipelagic to turbiditic and mass-gravity deposits has been recognized.